Stem cell research, regenerative medicine and challenges - Syed Muhammad Nazim; Sarfraz Ahmad (Journal of the Pakistan Medical Association, 2023)
Stem cell research and regenerative medicine have exponentially evolved in the past two decades. With the ability of cell renewal, unlimited expression and differentiation, stem cell research can potentially transform medical practice. Stem cells have different sources of origin and a wide range of potency ranging from unipotent to totipotent. Stem cell therapy can modify behavior of cells, generate differentiated tissues, and be used as a pharmacological intervention. Regenerative medicine is an emerging medical dedicated to reconstructing and repairing of and organs. Several challenges are to be addressed to allow transition of stem cell research from basic sciences to clinical practice. These obstacles include selection of appropriate stem cells with associated ethical concerns, manufacturing and processing of stem cells, genetic instability, lack of complete understanding of their mode of action at target sites, economic concerns, and lack of regulations of stem cell therapy. Key words: Medicine, Stem Cell, Totipotent, Transplantation